Selenium and vitamin E in relation to risk factors for coronary heart disease. Issue 2 (February 1984) - Ellis, N I; Lloyd, B; Lloyd, R S; Clayton, B E
Abstract : Fasting blood samples taken from 116 apparently healthy men aged 30-50 years were assayed for selenium, glutathione peroxidase activity, vitamin E, cadmium, lead, glucose, lipids, and albumin. Blood pressure was measured in each subject, and details of height, weight, smoking habits, and alcohol consumption were recorded. Multivariate analysis of the data showed that the decrease in blood and serum concentrations of selenium and the increase in whole blood cadmium concentrations in the cigarette smokers was independent of alcohol consumption. There was no correlation between blood selenium concentrations or glutathione peroxidase activities and the risk factors for cardiovascular disease. Neither alcohol consumption nor smoking had an effect on the vitamin E concentrations. There was a strong association, however, between vitamin E and serum lipid concentrations, although the increase in triglyceride concentrations in the smokers was not matched by a comparable increase in vitamin E. The possible role of selenium in the aetiology of heart disease remains unresolved.